SCHWARCZ, LILIA MORITZ. SOBRE O AUTORITARISMO BRASILEIRO. SÃO PAULO: COMPANHIA DAS LETRAS, 2019. - SALDANHA, Flavio Henrique Dias (Tempos Históricos, 2020)
SCHWARCZ, LILIA MORITZ. SOBRE O AUTORITARISMO BRASILEIRO. SÃO PAULO: COMPANHIA DAS LETRAS, 2019.